Metals Exposures of Residents Living Near the Akaki River in Addis Ababa, Ethiopia: A Cross-Sectional Study. (22nd November 2015) - Yard, Ellen; Bayleyegn, Tesfaye; Abebe, Almaz; Mekonnen, Andualem; Murphy, Matthew; Caldwell, Kathleen L.; Luce, Richard; Hunt, Danielle Rentz; Tesfaye, Kirubel; Abate, Moa; Assefa, Tsigereda; Abera, Firehiwot; et al.
Abstract : Background . The Akaki River in Ethiopia has been found to contain elevated levels of several metals. Our objectives were to characterize metals exposures of residents living near the Akaki River and to assess metal levels in their drinking water. Methods . In 2011, we conducted a cross-sectional study of 101 households in Akaki-Kality subcity (near the Akaki River) and 50 households in Yeka subcity (distant to the Akaki River). One willing adult in each household provided urine, blood, and drinking water sample. Results . Urinary molybdenum (p < 0.001 ), tungsten (p < 0.001 ), lead (p < 0.001 ), uranium (p < 0.001 ), and mercury (p = 0.049 ) were higher in Akaki-Kality participants compared to Yeka participants. Participants in both subcities had low urinary iodine; 45% met the World Health Organization (WHO) classification for being at risk of moderate iodine deficiency. In Yeka, 47% of households exceeded the WHO aesthetic-based reference value for manganese; in Akaki-Kality, only 2% of households exceeded this value (p < 0.001 ). There was no correlation between metals levels in water samples and clinical specimens. Conclusions . Most of the exposures found during this investigation seem unlikely to cause acute health effects based on known toxic thresholds. However, toxicity data for many of these metals are very limited.